Metabolic regulation of macrophages during tissue repair: insights from skeletal muscle regeneration. Issue 19 (17th June 2017) - Juban, Gaëtan; Chazaud, Bénédicte
Abstract : Macrophages are highly versatile cells that are involved both in the mounting and the resolution of inflammatory responses. Besides their properties in innate immunity to fight against pathogens, macrophages are essential for tissue repair, during which they adopt sequential inflammatory status. While the acquisition of some canonical polarized inflammatory statuses in vitro (M1/M2) is beginning to be understood at the molecular level, the regulation of macrophage skewing in vivo has been less investigated. Immunometabolism, in particular, is an emerging field, and most of the studies so far have investigated the control of macrophage polarization using in vitro set‐ups. In this context, skeletal muscle regeneration is an excellent paradigm to study tissue repair, since the sequential steps of inflammatory response and tissue repair are well characterized. In this Review, after introducing macrophage populations and functions during skeletal muscle regeneration, we present the current knowledge on the metabolic regulation of macrophage inflammatory status, with particular emphasis on the comparison between in vitro and in vivo models of macrophage activation. We also discuss the metabolic regulation of macrophages in vivo during skeletal muscle regeneration. Abstract :